Core self-evaluation as a mediator for social support and psychological well-being: A study of Indonesian migrant domestic worker candidates - Wardani, Laila Meiliyandrie Indah; Jeanne, Yanty; Mardhiyah, Muanawatul; Komarudin, Ade; Istiqomah,; Rozi, Fahrul (Kasetsart Journal of Social Sciences, 2021)
This study addresses the impact of social support on psychological well-being while investigating the role of core self-evaluation as a mediator among 1,455 Indonesian women migrant domestic worker candidates. The instruments of this study are Psychological Well-Being Scale (PWBS) medium version, Social Provision Scale (SPS), and Core Self-Evaluation Scale (CSES). The sampling technique is cluster sampling, and the analysis data used regression mediation model no.4 by Hayes. The results of this study show that core self-evaluation has a role as a partial mediator in the relationship between social support and psychological well-being. These significant effects can be obtained by psychological well-being if social support passes through core self-evaluation. This study looks like dew in the Sahara by addressing a crucial gap in research on Indonesian women migrant domestic workers with different cultural backgrounds as well as differing provisions regarding the regulations of migrant workers, primarily related to the psychological well-being of migrant domestic workers. core self-evaluation Indonesian migrant domestic worker psychological well-being social support